Analysis of the Influence of Fintech and Investor Trust on Investment Interest in Fore Coffee's e-IPO: Analisis Pengaruh Fintech dan Kepercayaan Investor terhadap Minat Investasi pada e-IPO Fore Coffee - Dharmawan; Desma Erica Maryati Manik (Sekolah Tinggi Ilmu Ekonomi Eka Prasetya, 2025)
The evolution of financial technology has revolutionized how individuals engage with monetary offerings, encompassing investment avenues. Because of the proliferation of diverse digital platforms offering investment options, people can now execute financial dealings with enhanced swiftness and effectiveness. The latest advancement in the realm of investment is the e-IPO or electronic initial public offering. This study delves into the influence of financial technology on the degree of investment interest in Fore Coffee's e-IPO, the impact of investor confidence on the propensity to invest in Fore Coffee's e-IPO, and how financial technology and investor trust collectively shape investment interest in Fore Coffee's e-IPO. The total population considered for this study encompassed all FORE Coffee investors, without a clearly defined count of respondents, with a sample group consisting of 130 individuals. The study's outcomes reveal that financial technology and investor trust significantly affect investment interest in Fore Coffee's e-IPO. Based on the t-test outcomes, both financial technology and investor trust exhibit a positive and significant influence on investment interest in Fore Coffee's e-IPO. The findings from the F-test demonstrate that financial technology and investor trust concurrently generate a positive and significant impact on investment interest in Fore Coffee's e-IPO. The extent of the combined effect of financial technology and investor trust on investment interest is quantified at 83.1%.